2020
DOI: 10.1016/j.lwt.2020.109787
|View full text |Cite
|
Sign up to set email alerts
|

Psyllium husk gel to reinforce structure of gluten-free pasta?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
2
17
1
1
Order By: Relevance
“…For the starchy gels, similar values were observed for all extracts apart from E3, where the lowest adhesiveness was found. The magnitudes of the adhesiveness were consistent with previous results for other food matrices[27,28]. The cohesiveness exhibited similar trends to those observed for firmness, although lower differences between the matrices prepared with both gelled agents were observed in this case (Figure5c).…”
supporting
confidence: 90%
“…For the starchy gels, similar values were observed for all extracts apart from E3, where the lowest adhesiveness was found. The magnitudes of the adhesiveness were consistent with previous results for other food matrices[27,28]. The cohesiveness exhibited similar trends to those observed for firmness, although lower differences between the matrices prepared with both gelled agents were observed in this case (Figure5c).…”
supporting
confidence: 90%
“…Raymundo et al (2014) also observed that psyllium husk significantly increases the strength of the dough, which results in better extensibility. Fradinho et al (2020) also added psyllium husk with rice flour to develop pasta and observed better extensible properties of the mixture.…”
Section: Texture Profile Analysis Of De-oiled Soy Flour Doughmentioning
confidence: 99%
“…Potato peel autohydrolysis liquid extract was processed with Psyllium husk: 4% w/w, dry basis (d.b.) at 40°C, 10 min to obtain a gel, at the conditions earlier described by Fradinho, Soares, Niccolai, Sousa, and Raymundo (2020). This gel was mixed with rice flour (50:50 ratio) in a thermoprocessor (Bimby TM31, Vorwerk, Wuppertal, Germany) at 25°C for 3 min.…”
Section: Fresh Pasta Preparation and Samplingmentioning
confidence: 99%